Toxic epidermal necrolysis associated with pembrolizumab. (July 2020) - Cai, Zhuo Ran; Lecours, Julie; Adam, Jean-Philippe; Marcil, Isabelle; Blais, Normand; Dallaire, Mario; Belisle, Annie; Mathieu, Alexandre
Introduction: Stevens-Johnson syndrome and toxic epidermal necrolysis are severe cutaneous drug eruptions characterized by epidermal detachment. Pembrolizumab is a monoclonal antibody that binds to the programmed death-1 receptor, and it has been associated with numerous cutaneous adverse side-effects, including Stevens-Johnson syndrome. Case report: We describe a 63-year-old male with metastatic lung adenocarcinoma who developed a rapidly progressing maculopapular rash three days after a first dose of pembrolizumab. On day 16, the rash affected more than 80% of body surface area with detachment of large sheets of necrolytic epidermis in 30–40% of body surface area. However, the patient only presented with mild mucosal involvement. Histopathologic examination of a skin biopsy showed a subepidermal blister with overlying prominent full thickness epidermal keratinocytic necrosis and a superficial perivascular infiltrate of lymphocytes. A toxic epidermal necrolysis secondary to pembrolizumab was then diagnosed. Management and outcome: In addition to supportive cares, the patient received corticosteroids and cyclosporine. The patient responded rapidly to the immunosuppressant therapy, and nearly complete re-epithelialization was achieved 24 days after the start of the reaction. Discussion: In our review of the literature, 15 other cases of Stevens-Johnson syndrome/toxic epidermal necrolysis were reported with programmed death-1/programmed cell death ligand-1 inhibitors. To our knowledge, this is the first case of toxic epidermal necrolysis secondary to pembrolizumab published in the literature. The American Society of Clinical Oncology guidelines suggest that cyclosporine, in addition to corticosteroids, be initiated when toxic epidermal necrolysis is suspected. Clinicians should be aware of this rare dermatological emergency with the increasing use of pembrolizumab in oncology.